Control of myopia using diffusion optics spectacle lenses: 12-month results of a randomised controlled, efficacy and safety study (CYPRESS) - Rappon, Joe; Chung, Carol; Young, Graeme; Hunt, Christopher; Neitz, Jay; Neitz, Maureen; Chalberg, Thomas (British journal of ophthalmology, 2023)
AbstractBackgroundMutations in the L/M cone opsin gene array cause abnormally high perceived retinal contrast and the development of myopia. Environmental factors may also lead to high visual contrast and cause myopia. Diffusion optics technology (DOT) lenses are designed to reduce contrast signalling in the retina and slow myopia progression.MethodsThe Control of Myopia Using Peripheral Diffusion Lenses Efficacy and Safety Study (CYPRESS, NCT03623074) is a 36-month, multicentre, randomised, controlled, double-masked trial evaluating two investigational spectacle lenses versus control lenses in myopic children aged 6–10, with a planned interim analysis at 12 months. The primary endpoints are change from baseline in axial length (AL) and spherical equivalent refraction (SER).Results256 children (58% female; mean age at screening, 8.1 years) were dispensed spectacles. Across all groups, baseline averages were AL 24.02 mm (SD±0.77 mm), SER −2.01 D (SD±0.9 D) using manifest refraction, and SER −1.94 D (SD±1.0 D) using cycloplegic autorefraction. At 12 months, mean difference in SER progression for test 1 versus control was −0.40 D (p<0.0001), representing a 74% reduction and −0.32 D for Test 2 (p<0.0001), representing a 59% reduction. The difference in AL progression for test 1 versus control was 0.15 mm (p<0.0001) and test 2 versus control was 0.10 mm (p=0.0018).Conclusion12-month results from this ongoing trial demonstrate the safety and effectiveness of DOT spectacles for reducing myopic progression.